Flexible Work Arrangement Factors That Affect Startup Employees in New Normal Situation - Akmalia; Gregorius, Prasetyo Adhitama (Jurnal Aplikasi Bisnis dan Manajemen, 2023)
Flexible Work Arrangement (FWA) is a work pattern implemented by companies with the aim of reducing the spread of the COVID-19 virus. The research was conducted to identify and measure the level of influence of FWA factors on employees in startup companies in the new normal situation. This research method was carried out using factor analysis. The research instrument was a questionnaire containing personal data and questions regarding FWA factors using Likert scale. Questionnaires were distributed via online platforms (WhatsApp and Instagram) using a non-probability sampling technique. 224 samples were collected and proceeded to the data processing stage using SPSS version 26 software. The results showed that were 5 FWA factors that influenced startup employees to work in the new normal situation. The factors are telecommuting factor, work location factor, policy and regulatory factor, company facilities factor, and personal factor. The conclusions of these findings were important for human relations and company management to understand the FWA factors that were considered beneficial for the business processes of startup companies, such as reducing operational costs and attracting the employee recruitment process. The practical implication for the management of startup companies was to observe and ensure that employees who applied the FWA work pattern were beneficial for their respective companies in achieving the company’s targets. Keywords: flexible work arrangement, work factors, work pattern, startup, new normal